ANALISIS LOYALITAS TOKO DENGAN PENDEKATAN SECOND ORDER FACTOR DARI STRUCTURAL EQUATION MODEL - Haryanto, Budhi; Kawuri, Winanti Retno (Journal of Business Strategy and Execution, 2010)
Objective of this study was to explain the shopping behavior. Shopper loyalty as dependent variable that was influenced by hedonic shopping motives and store attributes. In theÂ  model, gender, age, and income as variables that were designed to moderate the relationship of these variables. Sample size was 200 person taken from cusomer loyalty in Solo Grand Mall. Survey was conducted to improve the response rate of the sample. Structural Equation Model was used to examine the structural relation. Second order factor SEM was choosen in order to explain the linkage among of the obseved variable. The result showed that shopper loyalty was significanty influenced by store atributte and hedonic shoping motives. This sudy also indicated that gender, age, and income were found to moderate shopper loyalty forming process. In this study, insignificant results were also discused in order to give theoretically andÂ  practically implication.